2021
DOI: 10.1093/eurpub/ckab165.125
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of COVID-19 pandemic in vulnerable social groups in Athens, Greece

Abstract: Background The first case of SARS-CoV-2 in Greece was identified in February 2020. During the COVID-19 pandemic two lockdowns took place (March-May 2020/November 2020-ongoing). People who use drugs (PWUD), as well as the homeless, constitute vulnerable social groups. The main aim of this study is to assess the impact of social distancing measures during the COVID-19 pandemic on these groups. Methods A program was implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Shelters and overcrowding were associated with increased risk of COVID-19 infection and outbreak clusters compared to less crowded accommodation [ 38 , 42 , 44 , 56 , 57 , 59 ], rough sleepers [ 27 , 38 ], and food distribution sites [ 56 ]. Four studies that reported on COVID-19 prevalence did not have valid comparisons to interpret rates [ 44 , 51 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shelters and overcrowding were associated with increased risk of COVID-19 infection and outbreak clusters compared to less crowded accommodation [ 38 , 42 , 44 , 56 , 57 , 59 ], rough sleepers [ 27 , 38 ], and food distribution sites [ 56 ]. Four studies that reported on COVID-19 prevalence did not have valid comparisons to interpret rates [ 44 , 51 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that people experiencing homelessness reported feelings of loneliness or isolation during the COVID-19 pandemic [ 28 , 58 ]. Risk factors for loneliness included being male, living in crowded accommodation, and self-perceived risk of COVID-19 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research could be structured around risk scenarios—i.e., “baseline” when there is low incidence, “defend” when there are consistently rising levels of infection, and “outbreaks” in more localised or contained settings, as suggested, for example, in care home communities ( 61 ). Research should be also conducted reviewing the prevalence of long-term impacts of COVID-19 on people experiencing homelessness such as long COVID and mental wellbeing and interventions to mitigate these outcomes ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample consists of 628 (statistical power, 0.8 level; Ellis and Knaus, 1977; Roussos and Tsaoussis, 2020) social science university students, of which 78% were female and 22% were male. The students recruit with the convenient sampling method, and they voluntarily participate to this study.…”
Section: Methodsmentioning
confidence: 99%